Role of DNA repair in Bacillus subtilis spore resistance to high energy and low energy electron beam treatments. (May 2020) - Zhang, Yifan; Huber, Nina; Moeller, Ralf; Stülke, Jörg; Dubovcova, Barbora; Akepsimaidis, Georgios; Meneses, Nicolas; Drissner, David; Mathys, Alexander
Abstract: Bacillus subtilis spore inactivation mechanisms under low energy electron beam (LEEB) and high energy electron beam (HEEB) treatment were investigated using seven mutants lacking specific DNA repair mechanisms. The results showed that most of the DNA repair-deficient mutants, including Δ recA, Δ Ku Δ ligD, Δ exo Δ nfo, Δ uvrAB and Δ sbcDC, had reduced resistances towards electron beam (EB) treatments at all investigated energy levels (80 keV, 200 keV and 10 MeV) compared to their wild type. This result suggested DNA damage was induced during EB treatments. The mutant lacking recA showed the lowest resistance, followed by the mutant lacking Ku and ligD . These findings indicated that recA, Ku and ligD and their associated DNA repair mechanisms, namely, homologous recombination and non-homologous end joining, play important roles in spore survival under EB treatment. Furthermore, exoA, nfo, uvrAB, splB, polY1 and polY2, which are involved in nucleotide damage repair/removal, showed different levels of effects on spore resistance under EB treatment. Finally, the results suggested that HEEB and LEEB inactivate B. subtilis spores through similar mechanisms. This research will provide a better understanding of how EB technologies inactivate B. subtilis spores and will contribute to the application of these technologies as a non-thermal, gentle spore control approach. Highlights: Electron beam treatment induces DNA damage in bacterial spores. DNA repair is essential for bacterial spores to survive electron beam treatment. recA, Ku and ligD and associated DNA repair pathways are crucial for spore survival. exoA, nfo and uvrAB influence spore survival under electron beam treatment. High energy and low energy electron beams have similar spore inactivation mechanisms.